Chronic Metformin Therapy is Associated with a Lower Risk of Hemorrhoid in Patients with Type 2 Diabetes Mellitus - Tseng, Chin-Hsiao (Frontiers in Pharmacology, 2021)
Background: Metformin has anti-inflammatory property and reduces the risk of varicose vein in our previous study. Aim: To investigate the risk of hemorrhoid, another common disease involving the hemorrhoidal venous plexus, in ever versus never users of metformin in patients with type 2 diabetes mellitus. Methods: This is a population-based retrospective cohort study. Patients with new-onset type 2 diabetes mellitus during 1999-2005 were enrolled from Taiwan’s National Health Insurance. All patients who were alive on January 1, 2006 were followed up until December 31, 2011. Analyses were conducted in both an unmatched cohort of 152,347 ever users and 19,523 never users and in 19,498 propensity score (PS)-matched pairs of ever and never users. Traditional Cox regression and Cox regression incorporated with the inverse probability of treatment weighting (IPTW) using the PS were used to estimate hazard ratios. Results: New-onset hemorrhoid was diagnosed in 8211 ever users and 2025 never users in the unmatched cohort and in 1089 ever users and 2022 never users in the matched cohort. The hazard ratio for ever versus never users derived from the traditional Cox regression was 0.464 (95% confidence interval: 0.440-0.488) in the unmatched cohort; and was 0.488 (0.453-0.525) in the matched cohort. In the IPTW models, the hazard ratio was 0.464 (0.442-0.487) in the unmatched cohort and was 0.492 (0.457-0.530) in the matched cohort. A dose-response pattern was observed while comparing the tertiles of cumulative duration, cumulative dose and defined daily dose of metformin therapy to never users in all analyses. A risk reduction of approximately 40-50% was consistently observed in various sensitivity analyses. Conclusion: Chronic therapy with metformin in patients with type 2 diabetes mellitus is associated with a lower risk of hemorrhoid.